Make your bed little things that can change your life-- and maybe the world - McRaven, William H. (New York Hachette Audio, 2017)
Recounts tales from the author's life and from those of people he encountered during his military service who dealt with hardship with determination, compassion, honor, and courage.
Keywords: McRaven, William H. (William Harry), 1955---Anecdotes.